The role of physiological fitness factors contribution to performing of some basic handball skills for girl students of the College of Physical Education and Sport Sciences at University of Baghdad - Kahim, Mohammed Mahmood; Kahim, Mohammed Mahmood (International Journal of Psychosocial Rehabilitation, 2020)
The research community represented by students of the Faculty of Education Physical and Sport Sciences - University of Baghdad - the phase II of the academic year 20 1 4 -20 1 5. The researcher choose the sample random method of a b LGA number is a (20) student. And because the nature of the problem to be studied determines the method of research to be followed , so he must use the researcher The descriptive approach using the method of correlational studies for its suitability, the nature of this study and its objectives . After the search variables have been identified, well to know the percentage contribution of fitness elements physiological performance of some of the basic skills reel hand I use two types of tests to achieve this. Brother T. bars fitness physiological and ensure ((bend the trunk of the front of the stand - throw a medical ball (3 kg) hands of sitting on a chair - bend and extend the arms of the oblique lie (10 seconds) - triple jump stability - attachment mode D arms (even exhausting effort) - sitting from lying down (until exhausting effort) - the ability for (such as security) - ran 1500 meters)). And not Tests of skill , which included (( the speed of the handling on the wall for a period of 30 seconds from a distance of 4 m - Handling a rectangle drawn on preset - clapotement continued in a winding line for a distance of 30 m - correction of jumping high on the boxes)). The aim of the research is to identify the percentage of the contribution of the physiological fitness components to the performance of some basic handball skills among the subjects of the study sample. And the results showed (a lack of contribution to the elements of fitness physiological performance of the skill of handling. And there is a contribution in the anaerobic capacity characteristic and strength as fast as the muscles of the legs and the explosive power of the muscles of the arms, the performance of the skill of receipt and in the anaerobic capacity of aerobic performance skill clapotement and contributed to the flexibility the trunk and the explosive power of the arms’ muscles with the ability to shoot.